2021
DOI: 10.3390/met11111871
|View full text |Cite
|
Sign up to set email alerts
|

Early Crack Propagation in Single Tooth Bending Fatigue: Combination of Finite Element Analysis and Critical-Planes Fatigue Criteria

Abstract: Mechanical components, such as gears, are usually subjected to variable loads that induce multiaxial non-proportional stress states, which in turn can lead to failure due to fatigue. However, the material properties are usually available in the forms of bending or shear fatigue limits. Multiaxial fatigue criteria can be used to bridge the gap between the available data and the actual loading conditions. However, different criteria could lead to different results. The main goal of this paper is to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The most critical point and the severity of the damage were evaluated for both conditions exploiting the Findley fatigue criterion (Figure 6). The results for the reference non-treated gear are coherent with the experimental findings [57] showing a nucleation site in the "critical section" as defined by the ISO standard and with an early propagation direction of γ NP = 43 • . The shot-peened gear shows quite a different behaviour.…”
Section: Results Furthermore Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The most critical point and the severity of the damage were evaluated for both conditions exploiting the Findley fatigue criterion (Figure 6). The results for the reference non-treated gear are coherent with the experimental findings [57] showing a nucleation site in the "critical section" as defined by the ISO standard and with an early propagation direction of γ NP = 43 • . The shot-peened gear shows quite a different behaviour.…”
Section: Results Furthermore Discussionsupporting
confidence: 85%
“…The most reliable and effective method to take into account all these differences, is to use advanced fatigue criteria. This procedure was already used by the authors for determining the relation between STBF tests and real gears [23,[56][57][58][59].…”
Section: Stbf Testmentioning
confidence: 99%
“…Material Design & Processing Communications case and the actual case [23, 36-39, 52, 53]. On the one hand, the lack of the rolling/sliding condition implies that the loading condition occurring within the toot root is different [11,54,55]. On the other hand, the fact that the tests are performed on the teeth rather that gear implies a statistical difference [17,18].…”
Section: Gear Testing For Tooth Root Bending Fatiguementioning
confidence: 99%
“…The results revealed the relationship between the accelerations and the fatigue damage, as well as the mentioned characteristic parameters of the system. Franco Concli [ 31 ] evaluated the accuracy of five different criteria by applying them to different fractured gear specimens. The results showed that the criteria of the mechanical components agreed with determining the most critical node for gear geometries.…”
Section: Introductionmentioning
confidence: 99%